Analysis of Purchase Decisions for Counterfeit Fashion Products in E-Commerce - Jelita Puspita Wiyana; Iwan Kresna Setiadi; Yudi Nur Supriadi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research examines the impact of electronic word-of-mouth, Live Streaming, and Counterfeit Fashion Products, with Price acting as a moderator, on purchase decisions in Shopee e-commerce. The study employed SmartPLS SEM with 208 respondents. The findings reveal that Electronic Word of Mouth significantly positively influences purchase decisions by enhancing consumer trust and intentions. Counterfeit fashion products also positively impact purchase decisions, attracting consumers through affordable prices despite lower quality. Live streaming, as a promotional tool, significantly boosts purchase decisions by increasing consumer interest and trust through live demonstrations and real-time interactions. Price strengthens the relationship between interest in counterfeit fashion products and purchase decisions. These results highlight the crucial role of price, Electronic Word of Mouth, and live streaming in digital marketing strategies to drive purchase decisions in e-commerce.